GLYCEMIC CONTROL AND RELATED FACTORS IN TYPE II DIABETES PATIENTS IN THREE DIFFERENT HOSPITAL OUTPATIENT CLINICS IN ISTANBUL - (:unkn) unknown (NOBEL ILAC, 2010)
Objective: Evidences show that effective glycemic control is important in the management of diabetic patients. Our research aims to evaluate the efficacy of glycemic controls and and describe factors affecting glycemic control in three different hospitals in Istanbul. Material and Method: The research was descriptive, and conducted in three different public, private and university hospitals in Istanbul. Three hundred ninety-two outpatient type 2 diabetics were included to the study. Patients had type 2 diabetes for at least six months. Data were collected with a face to face questionnaire. Questionnaires included questions about patient's demographic characteristics, disease history, complications, disease management, and medical therapy information. Descriptive statistics, chi square and logistic regression were used in statistical analysis. Results: The mean age was 60.32 +/- 10.37 and the mean disease duration was 10.25 +/- 7.82 years. Mean HgbAlc level was 7.03 +/- 1.47, 59.2% of patients had a normal level. University hospital attendants were fount to have more normal mean HgbA 1 c level. University hospital patients had more normal HgbAl c levels (p<0.05). However, university hospital patients also had more complications; more diet lists and glucometric devices. State hospital patients were more obese. Private hospital patients had more diet lists and took adequate diabetic patient education. Patients with low education and low socioeconomic level, had no diet list, received insufficient diet list practicing, and obesity was related with high blood HgbAlc levels (p<0.05). In multivariate analysis, attending a hospital, socioeconomic level, having a diet list and practicing the diet list, and having glucometric devices were related with glycemic control quality. Conclusion: There were important differences between hospitals concerning glycemic control program outcomes. Education and socioeconomic level, diet list practicing and obesity control are important factors for type 2 diabetes management and hospital intervention programs should focus on these factors for diabetes management. There is a need for standardized diabetes management programs for hospitals.
Keywords: Diabetes mellitus; chronic disease; glycemic control; BLOOD-GLUCOSE; SELF-MANAGEMENT; GLYCOSYLATED HEMOGLOBIN; INTERVENTIONS; EDUCATION; CARE; COMPLICATIONS; FREQUENCY; BENEFITS; MELLITUS